Enhancement of large PV-integrated grid stability using an advanced UPQC - Kalal, Vijay Kumar; Byalihal, Shankaralingappa Channappa (Institute of Advanced Engineering and Science, 2025)
This paper presents an enhancement to the stability of large PV-integrated grids using an advanced power quality control system. The proposed unified power quality conditioner (UPQC) system control technique combines synchronous reference frame (SRF) theory and modified unit vector template generation (MUVTG), supplemented by an additional proportional-integral-derivative (PID) controller to regulate reactive power flow to the grid. The results indicate a reduction in the total harmonic distortion (THD) levels. The study also demonstrates the system’s stability for different harmonic orders and various cases of voltage sag and swell, in compliance with IEEE standards. The proposed approach effectively addresses power quality issues and achieves a THD of 0.30%, meeting the IEEE-519 standards using MATLAB Simulink.